Comparison of Sample Adequacy and Diagnostic Yield of 19- and 22-G EBUS-TBNA Needles. Issue 4 (October 2018) - Chaddha, Udit; Ronaghi, Reza; Elatre, Waafa; Chang, Ching-Fei; Mahdavi, Ramyar
Abstract : Background: The 2016 CHEST consensus guidelines recommend use of either 21- or 22-G needles for endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA). We decided to prospectively compare sample adequacy and diagnostic yield of the 19-G with the 22-G EBUS needle, hypothesizing that a larger gauge difference might magnify the differences between 2 needle sizes. Methods: Twenty-seven patients undergoing EBUS-TBNA at our institution were evaluated. All cases were performed by a single operator formally trained in interventional pulmonology. Both Olympus 19- and 22-G needles were used at each lymph node station in an alternating manner. Rapid on-site cytology evaluation was used and a separate cell block was prepared for each needle at each station. Results: Fifty-six lymph nodes were analyzed. Diagnoses included cancer (36%, including 1 lymphoma), reactive lymphoid tissue (53%), and sarcoidosis (11%). One hundred sixty-two and 163 passes were made with the 22- and 19-G needle, respectively. Sample adequacy was 73% and 46% with the 22 and 19-G needle, respectively ( P <0.001). Significantly fewer passes were bloody with the 22-G compared with the 19-G needle (19% vs. 59%; P <0.001). Diagnostic yield was not different between the 22- and 19-G needles (95% vs. 93%; P =0.62). Conclusion: In addition to no difference in diagnostic yield, the 19-G needle yielded samples that were frequently less adequate and more often bloody compared with the 22-G needle. Despite the larger caliber lumen, we conclude that the 19-G needle does not confer a diagnostic advantage.